Brachyury engineers cardiac repair competent stem cells. (24th October 2020) - Li, Mark; Yamada, Satsuki; Shi, Ao; Singh, Raman Deep; Rolland, Tyler J.; Jeon, Ryounghoon; Lopez, Natalia; Shelerud, Lukas; Terzic, Andre; Behfar, Atta
Abstract: To optimize the regenerative proficiency of stem cells, a cardiopoietic protein-based cocktail consisting of multiple growth factors has been developed and advanced into clinical trials for treatment of ischemic heart failure. Streamlining the inductors of cardiopoiesis would address the resource intensive nature of the current stem cell enhancement protocol. To this end, the microencapsulated-modified-mRNA (M 3 RNA) technique was here applied to introduce early cardiogenic genes into human adipose-derived mesenchymal stem cells (AMSCs). A single mesodermal transcription factor, Brachyury, was sufficient to trigger high expression of cardiopoietic markers, Nkx2.5 and Mef2c. Engineered cardiopoietic stem cells (eCP) featured a transcriptome profile distinct from pre-engineered AMSCs. In vitro, eCP demonstrated protective antioxidant capacity with enhanced superoxide dismutase expression and activity; a vasculogenic secretome driving angiogenic tube formation; and macrophage polarizing immunomodulatory properties. In vivo, in a murine model of myocardial infarction, intramyocardial delivery of eCP (600 000 cells per heart) improved cardiac performance and protected against decompensated heart failure. Thus, heart repair competent stem cells, armed with antioxidant, vasculogenic, and immunomodulatory traits, are here engineered through a protein-independent single gene manipulation, expanding the available regenerative toolkit. Abstract : Cardiopoietic stem cells are originally derived using a cocktail of cardiogenic growth factors. This study unveils the feasibility of achieving cardiopoiesis by a single gene (Brachyury) based induction of the human stem cell source. Engineered cardiopoietic stem cell progeny features pro-reparative traits and rescues heart failure postinfarction, introducing a scalable platform for regenerative therapy.